The State as the "Ultimate Parent": The Implications of Family for Racial and Ethnic Disparities in the Juvenile Justice System. (October 2022) - Goldman, Margaret; Rodriguez, Nancy
Racial and ethnic disparities permeate juvenile justice processing. Research attempting to explain these disparities has superficially considered the role of family measures in the differential treatment of youth of color. In particular, research has given little attention to the role of family supervision, despite its relevance to the mission of the juvenile court. Using attribution theory as a framework and data from three Arizona jurisdictions, we examine the effect of race/ethnicity on probation officers' attributions of family supervision; the effect of family characteristics, such as financial strain, parental incarceration, and family risk as measured by a risk assessment instrument, in shaping attributions of family supervision; and the effect of race/ethnicity, family characteristics, and attributions of family supervision on recommendations to formally or informally process youth. We find that attributions of family supervision are informed by race/ethnicity and family characteristics and that attributions of family supervision overwhelmingly drive probation officers' processing recommendations. Suggestions for improving policy and practice are discussed.